27 Incidence of sports-related injuries and illnesses in paralympic athletes – a prospective study during 52 weeks. (April 2019) - Fagher, Kristina; Dahlström, Örjan; Jacobsson, Jenny; Timpka, Toomas; Lexell, Jan
Abstract : Introduction: Sports-related injuries and illnesses in Paralympic sport (SRIIPS) is a growing concern, but knowledge about the etiology of SRIIPS is limited. The aim of this study was to prospectively assess the incidence and risk factors of SRIIPS among Swedish Paralympic athletes during 52 weeks. Materials and methods: 107 Paralympic athletes weekly reported SRIIPS in an eHealth application adapted to Paralympic athletes. Descriptive statistics and the Kaplan Meier method with corresponding Cox proportional hazards regression analysis (p<0.05) was used to assess incidence, time to SRIIPS, survival probability and hazard ratio (HR). Results: The incidence of injuries and illnesses was 7.0/1000 and 9.5/1000 hours of sport exposure, respectively. For injury the survival probability was 31.8% and median time to injury was 19 weeks (95% CI: 10.6–27.4). A higher risk to sustain an injury was noted among athletes;≥30 years (HR 1.6; 95% CI: 1.01–2.53), with previous severe injury (HR 2.4; 95% CI: 1.47–3.83), in team sports (HR 1.8; 95% CI: 1.10–2.80) and males (HR 1.8; 95% CI: 1.06–2.93). For illness, the survival probability was 23.4%. Median time to illness was 9 weeks (95% CI: 1.4–16.6). Athletes reporting an injury (HR 1.8; 95% CI: 1.08–2.98) and participants in team sports (HR 1.6; 95% CI: 1.05–2.54) had a higher risk for illness. Conclusion: This is the first longitudinal long-term prospective study of SRIIPS. Males, older athletes, athletes in team sports and with previous incidents are particularly at risk for injuries and illnesses and should therefore be targets for preventive measures and future research.